Proceedings of the 7th International Conference on Kansei Engineering and Emotion Research 2018 KEER 2018, 19-22 March 2018, Kuching, Sarawak, Malaysia (Advances in Intelligent Systems and Computing,, 2018)
The proceedings gather a selection of refereed papers presented at the 7th International Conference on Kansei Engineering and Emotion Research 2018 (KEER 2018), which was held in Kuching, Malaysia from 19 to 22 March 2018. The contributions address the latest advances in and innovative applications of Kansei Engineering and Emotion Research. The subjects include: Kansei, Emotion and Games Kansei, Emotion and Computing Kansei, Emotion and Wellbeing / Quality of Life Kansei, Emotion and Design Kansei, Emotion and Health / Ergonomics Kansei, Emotion and Multidisciplinary Fields Kansei, Emotion and Culture Kansei, Emotion and Social computing Kansei, Emotion and Evaluation Kansei, Emotion and User Experience The book offers a valuable resource for all graduate students, experienced researchers and industrial practitioners interested in the fields of user experience/usability, engineering design, human factors, quality management, product development and design.